THE ROLE MOTIVATOR AND STRATEGIES LITERACY LEARNING CRITICAL READING OF PRIMARY SCHOOL - Widada, Dwi Masdi (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Criticality creates curiosity in students. Students are taught to understand thinking patterns to recognize forms of language literacy. Students are expected to analyze knowledge, process information critically and reconstruct thinking patterns creatively. Students are taught to make decisions rationally in solving problems. Critical thinking is a way of exploring intelligence by comparing several things to reach conclusions in solving problems. Teachers can use various learning strategies so that students think critically. Reading is a bridge to see the development and progress of science. Education is part of scientific progress. Critical reading goes a long way in turning readers into creative researchers. Critical reading skills strengthen the ability to identify research strengths and weaknesses and highlight gaps in analysis. The ideas that emerge from this process help translate informed responses based on critical reading into future research studies that can advance science. Honing critical reading skills makes it possible to assess and integrate information into writing. Teachers have the potential to be students' learning partners in understanding creative and critical thinking patterns. Teacher strategies to develop a culture of critical thinking and critical reading to understand literacy are very important. There needs to be a special strategy in developing the concept of critical thinking. The strategies used include collaborative learning consisting of Cooperative Integrated Reading And Composition, Reading Tournament Strategy, Investigation Group Strategy, Critical Reading Jigsaw Strategy, Critical Schemata Strategy, and Persuasive Transformation Strategy. Reading literacy is understood as a form of contemporary discourse that students must have. The criticality of literacy as a discourse of science becomes a means for students to think creatively, find out and solve problems. The role of the teacher is to be a supporter in the learning process. The teacher's role as a guide and motivator is the main foundation in critical reading. The role of the teacher as a facilitator in critical reading learning is expected to gain student learning experience. The teacher's role is to facilitate students to have meaningful learning experiences.